Analysis of Garnier Men Consumers Perception Within "5 Steps of Consumer Purchase Decision Process" On male Undergraduate Student in Bandung - Yudha, Handry Martha; Hudrasyah, Herry (Journal of Business and Management, 2013)
Garnier MEN facial wash is one of the facial wash product in Indonesia launched in April 2011. Until 2012, other facial wash products keep popping up to try to attract the consumersâ€™ attention. Based on the â€œTop Brandâ€ award conducted by Frontier Consulting Group, in 2011 and 2012, Garnier MEN has not succeeded to at least get into the top 10 ranking for the â€˜facial washâ€™ category. The aim of this paper is to learn more about the Garnier MEN consumersâ€™ perception within â€œ5 steps of Consumer Purchase Decision Processâ€, to know whether the â€œEmotional Brandingâ€ factors affect consumer purchase decision, and whatâ€™s the most influential factors that influence their purchase decision. The results can be used for the Garnier MEN product development and marketing strategy to get more successful in the future. The data for this research were collected with in-depth interview from 8 respondents, and questionnaire from 204 respondents of Garnier MEN consumers. Results showed that the â€œEmotional Brandingâ€ factors (Promotion â€“ Brand Ambassador â€“ Packaging) â€œonlyâ€ affect the purchase decision in the amount of 30.06%, the remaining 69.94% affected by other factors. In conclusion, Garnier MEN must create a more attractive packaging design to increase consumersâ€™ attention, recommended for Garnier MEN to choose another public figure who has a characteristics like â€˜has a positive imageâ€™,â€˜represents the personality of active menâ€™, and also â€˜their achievement(s) can inspire people to follow themâ€™ to be the next Brand Ambassador, try to create a â€œCreative Outdoor Billboardâ€ to increase peopleâ€™s awareness, create more unique and attractive, but still elegantly TV ads, must gain more followers in the official Garnier MEN twitter account, always improve the quality of the product especially for the Garnier MEN â€œTurboLight Intensive Brighteningâ€ variant.Â Â Â Key-Words: Garnier Men, Purchase Decision Process, Emotional Branding, Facial Wash, Marketing Strategy